Patient-controlled analgesia morphine for the management of acute pain in the emergency department: a systematic review and meta-analysis - Muhammad Baihaqi Oon; Nik Hisamuddin Nik Ab. Rahman; Norhayati Mohd Noor; Mohd Boniami Yazid (International Journal of Emergency Medicine, 2024)
Abstract Background The ideal pain control approach is typically viewed as titration of analgesia for pain reduction and periodic pain evaluation. However, this method takes time and is not always possible in the crowded Emergency Department. Therefore, an alternative way to improve pain care in the Emergency Department is needed to avoid this unpleasant sensation in the patients. The best solution to tackle this situation is using Patient Controlled Analgesia (PCA), in the form of a PCA pump. Study objectives This systematic review and meta-analysis was designated to evaluate the efficacy of PCA morphine in treating acute pain at Emergency Department. Methods We searched databases Cochrane Central Register of Controlled Trials (CENTRAL), Medline, and Google Scholar up to February 2022 and identified randomized controlled trials with English language only that compare PCA morphine to IV morphine in treating patients presenting with acute pain at Emergency Department. Results Eight trials were included in our review, comprising 1490 participants. We compared PCA morphine vs. IV morphine. There were no differences in the pain score between PCA and IV morphine (standard mean difference [SMD] = -0.20, p = 0.25). Further subgroup analyses (origin of the pain, time of assessment and the durations) showed no difference except for the dosages as the PCA morphine reduced the pain compared to IV morphine in low and high dosages but only two studies were involved. However, the analysis showed PCA morphine increased patient satisfaction and reduced the number of patients who required additional analgesia compared to IV morphine (MD 0.12, P < 0.001), (MD 0.47, P < 0.001) respectively. Data obtained in this review pertaining to adverse effects such as nausea, vomiting, pruritus, and drowsiness is limited since not all the trials reported the events. Conclusions PCA morphine do appear to have a beneficial effect on the outcome of patient satisfaction and the number of patients who required additional analgesia. However, further studies targeting a larger sample size is required to increase the certainty of the evidence.